RNA modifications in human diseases: what, when and how? - Yi, Chengqi (Henry Stewart Talks, 2021)
RNA modifications in Human Disease, Pseudouridine, Molecular Genetics, Cancer Genetics, Epitranscriptomics, Gene Regulation, Research Methodology